PELANGGARAN STANDAR TEMPAT PENAHANAN ANAK DALAM PUTUSAN NOMOR 8/PID.SUS-ANAK/2025/PN JKT.SEL: Violations of Standarts For Child Detention Places in Decision Number 8/Pid.Sus-Anak/2025/PN Jkt.Sel - Maria Angelina Butar Butar; Setiyono (Reformasi Hukum Trisakti, 2026)
The detention of children facing in the Law is an important issue in the Juvenile Criminal Justice System because it concerns restrictions on the freedom of subjects who are obliged to receive special protection. Even though the Law regarding the Juvenile Criminal Justice System states that children should only be detained as a last option and must be held in a Temporary Child Placement Institution or a Social Welfare Implementation Institution, the actual practice does not always follow these rules. The issue at hand is how to detain minors who are in legal trouble according to the guidelines set forth in Law Number 11 of 2012 about the Juvenile Criminal Justice System. The method of investigation adopted is a normative legal approach employing deductive reasoning. The findings from the discussion and conclusions indicate that the placement of minors in the State Detention House in this instance does not align with the standards for child detention, as it contradicts the principle of prioritizing the best interests of the child and the requirement to separate them from adult detainees. Thus, the practice exhibits procedural and substantial breaches that call for enhancements in its execution